Biosynthesis of silver nanoparticles by the fungus Arthroderma fulvum and its antifungal activity against genera of Candida, Aspergillus and Fusarium - Xue B (Dove Medical Press, 2016)
Baiji Xue,1 Dan He,1 Song Gao,1 Dongyang Wang,1 Koji Yokoyama,2 Li Wang1 1Department of Pathogenobiology, Jilin University Mycology Research Center, Key Laboratory of Pathobiology, Ministry of Education, College of Basic Medical Sciences, Jilin University, Changchun, People’s Republic of China; 2Medical Mycology Research Center, Chiba University, Chiba, Japan Abstract: The objective of this study was to find one or more fungal strains that could be utilized to biosynthesize antifungal silver nanoparticles (AgNPs). Using morphological and molecular methods, Arthroderma fulvum was identified as the most effective fungal strain for synthesizing AgNPs. The UV–visible range showed a single peak at 420 nm, which corresponded to the surface plasmon absorbance of AgNPs. X-ray diffraction and transmission electron microscopy demonstrated that the biosynthesized AgNPs were crystalline in nature with an average diameter of 15.5±2.5 nm. Numerous factors could potentially affect the process of biosynthesis, and the main factors are discussed here. Optimization results showed that substrate concentration of 1.5 mM, alkaline pH, reaction temperature of 55°C, and reaction time of 10 hours were the optimum conditions for AgNP biosynthesis. Biosynthesized AgNPs showed considerable activity against the tested fungal strains, including Candida spp., Aspergillus spp., and Fusarium spp., especially Candida spp. Keywords: silver nanoparticles, fungi, antifungal activity, nanomedicine